New prospects in the treatment of diabetes mellitus - Minara Shamkhalovna Shamkhalova (Endocrinology Research Centre, 2012)
Cardiovascular complications, a major cause for disability and morbidity in diabetes mellitus (DM), constitute the greatest threat of the diabetes epidemic. Glycemic stability within the therapeutic targets is a prerequisite to prevention of micro- and macrovascular complications of DM. Traditional therapies are aimed at cardinal defects determining development of type 2 diabetes mellitus (T2DM). Unfortunately even in combination they fail to deliver long-term glycemic control without stimulation of weight gain and increase in hypoglycemic risks with negative cardial, renal and hepatic impact. Preservation of beta-cell secretion capacity is also hardly attainable. Incretin-based therapy is a novel, actively developed approach that influences gut hormone physiology for better glycemic control. So far research efforts have yielded two classes of drugs: GLP-1 mimetics and DPP-4 inhibitors. Both are regarded nowadays for a number of important benefits, including beta-cell function improvement, adjusted to human physiology (i.e. stimulation of insulin secretion ?as needed? by the body, - hence low hypoglycemic risk). They also feature positive cardiovascular and body weight effects, thereby taking an important position in complex DM treatment.